Natural disasters and their impacts on the silica losses from agriculture in China from 1988 to 2016. (February 2020) - Zheng, Dexiang; Zhang, Heng; Yuan, Yuze; Deng, Zhong; Wang, Ku; Lin, Geng; Chen, Yi; Xia, Jiangjiang; Jin, Shao-Fei
Abstract: Natural disasters play significant destructive roles in agricultural production. Agriculture has substantially altered the biogeochemical silica cycle via the harvest of the grain and straw of silica-rich crops. China is a developing agricultural country that experiences frequent natural disasters. Although the spatiotemporal changes in the occurrence of natural disasters are well known for individual disaster events, the study of the effects of multiple disasters on cereal crop productivity and the resultant silica harvest is still relatively new. To make the connection between natural disasters and the silica biogeochemical cycle, we compiled a dataset of natural disasters and crop production and silicon contents in cereal crops (rice, wheat, and maize) in China using province-level data from 1988 to 2016. Our results show that the area affected by natural disasters declined significantly after 2000, and changes in the area affected by natural disasters varied at the province level. From 1988 to 2016, the total silica losses from grain and straw harvests due to natural disasters were 7.14 and 53.10 million tons, respectively. Half of the silica loss in more than half of the provinces was caused by drought. Our study suggests that drought prevention will increase the size of the silica sink and thereby increase the size of the carbon sink in China's agriculture. Highlights: Cultivation area affected by natural disasters declined significantly after 2000 in China. Changes in affected areas of natural disasters varied at provincial level in China from 1988 to 2016. Annual silica loss due to natural disasters from grain and straw harvest was 0.24 and 1.83 million tons, respectively.